Pengaruh Motivasi Kerja dan Work Life Balance Terhadap Kinerja Pegawai di mediasi Komitmen Organisasi: Studi pada Pegawai DPUPR Kabupaten Batang - Ronggo Prasetyo; Lie Liana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of work motivation and work-life balance on employee performance, mediated by organizational commitment. The population in this study was 412 employees of the Batang Regency Public Works and Housing Agency (DPUPR), with a sample size of 120 drawn using the Roscoe formula (1975). Sampling was conducted using purposive sampling with the criterion of employee tenure exceeding one year. Data were processed using SPSS version 22 software. Data analysis techniques included respondent descriptions, variable descriptions, validity tests, reliability tests, F-tests, R2-tests, t-tests, and mediation tests using path analysis. The results indicate that work motivation has a positive effect on organizational commitment, work-life balance has a positive effect on organizational commitment, organizational commitment has a positive effect on employee performance, work motivation has a positive effect on employee performance, work-life balance has no effect on employee performance, organizational commitment mediates the effect of work motivation on employee performance, and organizational commitment mediates the effect of work-life balance on employee performance.